Effect of smear layer deproteinization with chemo-mechanical caries removal agents on sealing performances of self-etch adhesives - Kusumasari, Citra; Abdou, Ahmed; Tichy, Antonin; Hatayama, Takashi; Hosaka, Keiichi; Foxton, Richard M; Wada, Takahiro; Sumi, Yasunori; Nakajima, Masatoshi; Tagami, Junji (Journal of dentistry, 2020)
OBJECTIVES: To evaluate the sealing performance of self-etch adhesives (SEA) after smear layer deproteinization with chemo-mechanical caries removal agents (CRA) to enamel and dentin cavity walls in comparison with 6% NaOCl smear layer deproteinizing. METHODS: Eighty extracted bovine incisors with tapered cylindrical cavities (2.5 mm upper diameter, 1.5 mm lower diameter, 2 mm depth) at the cemento-enamel junction were randomly divided into four pre-treatment groups; no treatment (control), Papacarie (papain enzyme-based CRA), Carisolv (NaOCl-based CRA), and 6% NaOCl. After pretreatment, G-Bond Plus (GBP, one-step SEA) or Clearfil SE Bond 2 (CSE, two-step SEA) was applied to the pre-treated cavity, and then filled with a flowable resin composite (Clearfil Majesty ES Flow). Gap formations at the enamel and dentin lateral walls, and on the dentin cavity floor were investigated using swept-source optical coherence tomography (SS-OCT) after 24-h water storage at 37 °C. Deproteinizing effects of the tested agents on smear layer-covered enamel and dentin were quantified by changes in the amide:phosphate ratio using ATR-FTIR analysis. RESULTS: Papacarie significantly reduced gap formation with both self-etch adhesives at all locations, compared to the control group (p < 0.05). In contrast, increased gap formation was observed with Carisolv and NaOCl. In most groups, CSE exhibited significantly lower gap formation than GBP (p < 0.05). ATR-FTIR revealed a significant decrease in the amide:phosphate ratio for all the deproteinizing agents (p < 0.05). CONCLUSIONS: Chemo-mechanical CRAs could effectively remove the organic phase of enamel and dentin smear layer. The papain enzyme-based gel Papacarie could improve the sealing performance of the self-etch adhesives to both enamel and dentin.
Keywords: Smear Layer; Composite Resins; Resin Cements; Smear layer deproteinizing; Dentin-Bonding Agents; testování materiálů; smear layer; zvířata; Dentin; NaOCl-based gel; pryskyřičné cementy; vazba zubní; Sealing performance; zubní sklovina; složené pryskyřice; zubní cementy; Adhesives; Cattle; Dental Bonding; Chemo-mechanical; skot; Self-etch; dentinová adheziva; Dental Cements; Animals; Papain enzyme-based gel; Dental Enamel; adheziva; Materials Testing; dentin